Waste Pollution from the Jeans Factory in Karangdowo Village, Pekalongan Regency, in 1997 - Adnin Malika Anggun Mulia Dacasta; Ibnu Shodiq (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This article examines the environmental pollution conflict caused by the activities of a jeans washing factory in Karangdowo Village, Kedungwuni District, Pekalongan Regency in 1997. The main issues of the study include changes in environmental quality due to industrial waste, the social response of residents to the pollution of wells and rice fields, and the dynamics of the relationship between the community, entrepreneurs, and the government in resolving the conflict. This study aims to analyze the impact of small-scale industrialization on the village settlement environment, the forms of community resistance, and the dispute resolution mechanisms pursued. The method used is the historical method with heuristic, verification, interpretation, and historiography stages, through the use of primary sources in the form of contemporary newspapers and archival documents, as well as secondary sources in the form of books and scientific articles. The results of the study show that the disposal of waste without adequate treatment has caused a decline in well water quality and triggered social tensions. Deliberation efforts did not result in an agreement, so residents took civil and criminal legal action. This case shows the weakness of environmental supervision and the bargaining position of the community in dealing with local industry.